A randomized, placebo-controlled, single ascending-dose study to assess the safety, tolerability, pharmacokinetics, and immunogenicity of subcutaneous tralokinumab in Japanese healthy volunteers. Issue 3 (June 2018) - Baverel, Paul; She, Dewei; Piper, Edward; Ueda, Shinya; Yoshioka, Tomoko; Faggioni, Raffaella; Gevorkyan, Hakop
Abstract: Tralokinumab is a human monoclonal antibody in clinical development for asthma and atopic dermatitis that specifically neutralizes interleukin-13. This phase I, single-blind, randomized, placebo-controlled, single ascending-dose study assessed the safety, tolerability, pharmacokinetics (PK), and immunogenicity of subcutaneous tralokinumab (150, 300, or 600 mg) in thirty healthy Japanese adults. The most frequent treatment-emergent adverse event (TEAE) in all treatment groups was injection-site pain. The frequency and severity of TEAEs was similar across tralokinumab doses. Cmax, AUC(0–t), and AUC(0–inf) increased in a dose-proportional manner, and mean t1/2 ranged from 20 to 25 days. No anti-drug antibodies were detected. A post-hoc pooled population PK modeling analysis, incorporating PK data from this study, demonstrated that Japanese individuals had greater systemic exposure to tralokinumab than non-Japanese individuals. This difference was not clinically relevant and was primarily due to differences in body weight, with lower body weight associated with greater PK exposure. Japanese ethnicity was not a significant predictor of tralokinumab PK. This study indicates that single-dose subcutaneous administration of tralokinumab 150–600 mg was well tolerated in Japanese healthy volunteers, and supports the 300 mg dose selection for Japanese patients with asthma in ongoing clinical trials. Graphical abstract: